Magnetic properties of iron-rich Fe-Zr glasses - COEY, JOHN MICHAEL DAVID (American Physcial Society, 1987)
A systematic study of the magnetic properties of melt-spun amorphous FexZr100-x alloys with 88?x?93 using Mossbauer and magnetization measurements has established the magnetic phase diagram. The ordering temperature Tc falls sharply with increasing x; below a second transition Txy, associated with the freezing of transverse-spin components, all the alloys order asperomagnetically (Txy<Tc). Hysteresis appears at still lower temperatures, but it is not directly related to the transverse-spin freezing. A T1.3 variation of hyperfine field observed for T<Txy is attributed to excitation of transverse magnetic modes. Contrary to the predictions of Heisenberg spin-glass theory, neither the ferromagnetic nor the asperomagnetic order appears to be long range. Extrapolation to x=100 indicates that pure amorphous iron would be a speromagnet with an iron moment of 1.7?B and a spin-freezing temperature of order 150 K. Upon hydrogenation the magnetic structures of all the a-Fe-Zr alloys lose their noncollinear character, becoming good ferromagnets with Curie points in excess of 400 K.
PUBLISHED
Keywords: Physics